Factors affecting target caloric achievement and calorie intake improvement: the nutrition support team's role - Bong, Jeong Bin; Kim, So-Yeong; Ryu, Han Uk; Kang, Hyun Goo (Frontiers in Nutrition, 2024)
Background The nutrition support team (NST) works to improve malnutrition in hospitalized patients, and its role is expanding as more hospitals adopt NST. This study aimed to identify the clinical characteristics of NST-referred patients admitted to a tertiary hospital. The study focused on two groups: those who achieved the target calories, approximately 75% or more of their caloric needs relative to their body weight regardless of the period after the first NST referral, and those who improved their calorie intake 1 week after NST therapy. This study also analyzed the important factors affecting the achievement of target calorie intake and improvement in calorie intake to discover the focus of future NST therapy. Methods This study examined 1,171 adult patients (aged ≥18 years) who were referred to the NST from all the departments within a tertiary hospital at least twice, with a minimum one-week interval between referrals, between January 1, 2019, and December 31, 2020. The study participants consisted of patients receiving <75% of their required caloric intake at the time of their first NST referral. Patients were categorized and compared according to whether they achieved their target calorie intake regardless of the period after the first NST referral and whether they improved their calorie intake 1 week after the NST therapy. We then identified factors affecting target caloric achievement and improvement in calorie intake. Results The group that achieved the target calorie intake had a lower proportion of neuro department patients (31.3%), a higher proportion of patients receiving intensive care unit (ICU) care (31.9%), and a longer ICU stay (p < 0.001) than the group that did not achieve the target calorie intake. Neuro department admission negatively affected target caloric achievement [adjusted odds ratio (aOR) = 0.305, 95% confidence interval (CI) = 0.150–0.617], whereas the length of ICU stay positively affected target caloric achievement (aOR = 1.025, 95% CI = 1.007–1.043). The proportion of neuro department patients was also low (42.5%) in the group with improved calorie intake 1 week after NST therapy. Neuro department admission was a negative factor (aOR = 0.376, 95% CI = 0.264–0.537) affecting the improvement in calorie intake. Conclusions NST therapy significantly improved clinical outcomes for inpatients at nutritional risk. Because achieving target calories and improving calorie intake in neuro department patients is difficult, it is necessary to actively refer them to NST to achieve the target calories and improve calorie intake. Furthermore, because a longer ICU stay positively affects target calorie achievement, the system for ICU nutrition therapy should be expanded and implemented for general-ward patients, including neurological patients.